Prevalence and antimicrobial susceptibility of enterococcus species isolated from clinical specimens. - Akhter, S; Asna, ZH; Rahman, MM (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):694-9 The abstract of this article is available on the PubMed website